Evaluation of Risk Factors Influencing Tick-Borne Infections in Livestock Through Molecular Analyses - Lorena Cardillo; Claudio de Martinis; Giovanni Sgroi; Alessia Pucciarelli; Gerardo Picazio; Maurizio Viscardi; Luisa Marati; Maria Ottaiano; Roberta Pellicanò; Nicola D’Alessio; Vincenzo Veneziano; Giovanna Fusco (Microorganisms)
Climate changes and human-related activities are identified as major factors responsible for the increasing distribution and abundance of vectors worldwide and, consequently, of vector-borne diseases (VBDs). Farmed animals, during grazing or in establishments with the absence of biosecurity measures, can easily be exposed to wildlife showing high-risk of contagion of several infectious diseases, including VBDs. Furthermore, livestock represents an interface between wildlife and humans, and thus, promoting the transmission pathway of VBDs. Little is known about the presence and prevalence of VBDs in livestock in Southern Italy; therefore, the present study evaluated the circulation of zoonotic VBDs in livestock and potential risk of exposure. A total of 621 whole blood samples belonging to cattle and buffaloes (n = 345) and small ruminants (n = 276) were examined by molecular examinations for the detection of tick-borne pathogens (TBPs). High prevalence (66.3%) for at least one agent was observed. Moreover, the risk of exposure related to environmental features was assessed, as follows: presence of humid areas, high-density of animals, and sample collection during May. These results show a high circulation of TBPs among livestock and underline the need for surveillance in high-risk habitats for public health.